EXPLORING THE PERCEIVED SUCCESS OF A STRATEGIC MEDICAL TOURISM ALLIANCE FROM THE PATIENTS’ PERSPECITIVE - Zhang, Xizi; P. Wall, Dr William; Hughes, Dr Kate (AIBPM Publisher, 2018)
This paper examines the customer experience of a medical tourism alliance project between a Chinese private hospital and a Thai medical center. The purpose is to evaluate the perceived value of this strategic project from the perspective ofthe patients. Qualitative data were collected through a series of interviews with Chinese patients while they were in Thailand receiving medical treatment. Additional interviews collected data from informed experts involved in the memorandum of understanding (MOU); to gain their perspective on the alliance’s success. Secondary data wassourcedfrom reports available from the hospital, medical center, business media, and scholarly publications to supplement the primary information. This paper explores the voice of the customer as an indicator of post-project success.